2021
DOI: 10.3390/pathogens10121542
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Hepatitis E Virus Infection in Semi-Domesticated Eurasian Tundra Reindeer (Rangifer tarandus tarandus) in Norway

Abstract: Hepatitis E virus (HEV) is a common cause of viral hepatitis in humans. In developing countries, HEV-infections seem to be mainly associated with pigs, but other animal species may be involved in viral transmission. Recently, anti-HEV antibodies were detected in Norwegian wild reindeer. Here, we investigated anti-HEV seroprevalence in Norwegian semi-domesticated reindeer, animals in closer contact with humans than their wild counterparts. Blood samples (n = 516) were obtained from eight reindeer herds during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
2
5
0
3
Order By: Relevance
“…The significance of deer for the epidemiology of HEV is confirmed by numerous data on the prevalence of anti-HEV antibodies in various deer species from different parts of the world [ 5 ], including areas where suides are absent or rare. Thus, anti-HEV antibodies were detected in tundra wild and semidomesticated reindeer in Norway, Russia and Canada [ 23 , 24 , 25 , 26 ], indicating the possible HEV circulation in this deer species without transmission from suides. Moreover, the recent data indicate that HEV-3 infection in roe and fallow deer is characterized by histopathological changes indicative of mild lymphocytic inflammation similar to those observed in other host species, with the amount of viral RNA in liver tissue comparable to that observed in wild boars [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The significance of deer for the epidemiology of HEV is confirmed by numerous data on the prevalence of anti-HEV antibodies in various deer species from different parts of the world [ 5 ], including areas where suides are absent or rare. Thus, anti-HEV antibodies were detected in tundra wild and semidomesticated reindeer in Norway, Russia and Canada [ 23 , 24 , 25 , 26 ], indicating the possible HEV circulation in this deer species without transmission from suides. Moreover, the recent data indicate that HEV-3 infection in roe and fallow deer is characterized by histopathological changes indicative of mild lymphocytic inflammation similar to those observed in other host species, with the amount of viral RNA in liver tissue comparable to that observed in wild boars [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even though a lack of specificity of the serological assay employed could be considered, as was also observed in the study of Rutjies et al [ 86 ], in which an overestimated prevalence for deer species was suspected, it cannot be excluded that there could be unknown sources of HEV infection for wild ruminants [ 98 ]. Rinaldo et al [ 99 ] suggested the possibility that hares and rats could potentially have been involved in the transmission of HEV to Norwegian semi-domesticated reindeer in an area in which wild boars have never been observed [ 99 ]. The roles of rodents in HEV infections have been repeatedly investigated, mostly on pig farms due to their potential abundance on farms.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several serological and molecular investigations have been conducted in different species of wild ruminants belonging to the Cervidae and Bovidae families, demonstrating their important roles as HEV hosts. Studies mainly focused on cervid species, commonly referred to as deer, have revealed seroprevalence rates ranging from 0.2 to 12% in Asia [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ], 1.7% to 62.7% in America [ 82 , 83 , 84 ] and 0.4% to 19.5% in Europe [ 64 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], with reported HEV RNA prevalences of 0.06–35.0% [ 78 , 79 , 102 ], 0% [ 84 ] and 1.2–34.1% [ 48 , 49 , 51 , 85 , 86 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 103 , 104 ,…”
Section: Wild Ruminantsmentioning
confidence: 99%
“…Reindeer are adapted to colder climates than other deer species, having a wider distribution from the coast to higher altitudes, both in the Taiga and Tundra areas (Nowak, 1999). Reindeer have been documented to support enzootic maintenance of viruses like herpesvirus, pestivirus and Hepatitis E virus (Rinaldo et al, 2021; Romano et al, 2021; Sacristán et al, 2021; Tryland et al, 2021). Recently, antibodies against Inkoo virus and Inkoo virus‐specific RNA were detected in reindeer for the first time in Norway which indicates that reindeer are exposed to a wide range of viruses (Shakya et al, 2022).…”
Section: Introductionmentioning
confidence: 99%